The roles and training of primary care doctors: China, India, Brazil and South Africa - Mash, Robert (Hum Resour Health, 2015)
China, India, Brazil and South Africa contain 40% of the global population and are key emerging economies. All these countries have a policy commitment to universal health coverage with an emphasis on primary health care. The primary care doctor is a key part of the health workforce, and this article, which is based on two workshops at the 2014 Towards Unity For Health Conference in Fortaleza, Brazil, compares and reflects on the roles and training of primary care doctors in these four countries. Key themes to emerge were the need for the primary care doctor to function in support of a primary care team that provides community-orientated and first-contact care. This necessitates task-shifting and an openness to adapt one’s role in line with the needs of the team and community. Beyond clinical competence, the primary care doctor may need to be a change agent, critical thinker, capability builder, collaborator and community advocate. Postgraduate training is important as well as up-skilling the existing workforce. There is a tension between training doctors to be community-orientated versus filling the procedural skills gaps at the facility level. In training, there is a need to plan postgraduate education at scale and reform the system to provide suitable incentives for doctors to choose this as a career path. Exposure should start at the undergraduate level. Learning outcomes should be socially accountable to the needs of the country and local communities, and graduates should be person-centred comprehensive generalists.